Corrigendum: Development and Cross-Validation of a Predictive Equation for Fat-Free Mass in Brazilian Adolescents by Bioelectrical Impedance (Front. Nutr., 2022 9 820736 10.3389/Fnut.2022.820736) - De Moraes-Ferrari, G (Frontiers Media S.A., 2023)
In the original article, there was a mistake in Table 4 as published. The article included a table referring to another mathematical model, which does not refer to this study. The corrected Table 4 appears below. In the original article, there was an error on page 5 in the section Results. In the presentation of the mathematical model for FFM estimation, the word “Fri” appears instead of the word “Sex.” The corrected mathematical model included is presented below: FFM = − 17.189 + 0.498 (Height2/Resistance) + 0.226 Weight + 0.071 Reactance − 2.378 Sex + 0.097 Height + 0.222 Age Sex: male = 0; female = 1 The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated. © 2023 Costa, Silva, Masset, Cesário, Cabral, Ferrari and Dantas.